Profil Cedera Olahraga Atlet Rugby 7’s Putra Kabupaten Grobogan pada Babak Kualifikasi PORPROV 2025 - Risqi, Ananta Maulana; Warthadi, Anugrah Nur; Sudarmanto, Eko (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This study aims to analyze the injuries experienced by athletes during the qualification round of the 2025 Central Java Provincial Sports Week (Porprov). This research utilizes a quantitative descriptive approach, with the subjects being all 12 male rugby 7s athletes from Grobogan Regency, including substitute players. Data collection procedures were conducted through observations and questionnaires, using an instrument in the form of a questionnaire containing statements regarding the injuries experienced by the athletes. Data analysis was performed by grouping the data and calculating it using a percentage formula. The results of the study indicate that the majority of injuries occurred in the lower extremities, with the dominant types of injuries being abrasions and muscle contusions resulting from physical contact. It can be concluded that rugby 7s at the regency qualification level carries a high risk of injury, thus necessitating a planned and survey-based injury prevention strategy.